Intracardiac Embolized Prostate Brachytherapy Seeds: Imaging Features in Patients Undergoing Electrocardiogram-Gated Cardiac Computed Tomography. Issue 4 (July 2016) - Halpenny, Darragh F.; Latson, Larry; Mason, Derek; Donnino, Robert; Alpert, Jeffrey; Jacobs, Jill E.
Abstract : Objective: This study aims to provide the first description of the computed tomographic (CT) appearances of intracardiac embolized brachytherapy seeds in patients undergoing electrocardiogram (ECG)-gated cardiac CT. Methods: The institutional Picture Archive and Communication System was searched for male patients who underwent enhanced ECG-gated cardiac CT, and reports were searched for the key words "metallic, " "prostate, " "brachytherapy, " "radiation, " "embolized, " and "radioactive." Each study was identified and examined for an intracardiac metallic object conforming to the size of a prostate seed. Results: Between January 01, 2005, and June 30, 2014, a total of 3206 male patients underwent ECG-gated cardiac CT. Five patients (0.15%) had a history of prostate cancer and an intracardiac metallic object with CT imaging characteristics consistent with an embolized prostate seed. In all 5 patients, the seeds were embedded in the trabeculations of the inferior aspect of the basal right ventricular free wall. Conclusions: Intracardiac embolized brachytherapy seeds appear as small objects with surrounding metallic artifact characteristically embedded in the inferior aspect of the basal right ventricular free wall.